2009
DOI: 10.1590/s1516-635x2009000100007
|View full text |Cite
|
Sign up to set email alerts
|

Calcium and available phosphorus levels for laying hens in second production cycle

Abstract: This experiment studied the effect of four calcium (3.0, 3.5, 4.0, and 4.5%) and four available phosphorus levels (0.25, 0.30, 0.35, and 0.40%) in the diet of semi-heavy commercial layers after molting. Hisex Brown® layers between 90 and 108 weeks of age were distributed in a completely randomized experimental design with a 4x4 factorial arrangement with 16 treatments of five replicates of eight birds each. mortality, egg production, feed intake, egg mass, average egg weight, calcium and phosphorus intake, fee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
47
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(55 citation statements)
references
References 26 publications
6
47
0
2
Order By: Relevance
“…The results for shell weight, specific gravity and number of eggs discarded are similar to those obtained by Murata et al (2009), who also did not observe influence from the calcium levels (37.5; 41.5 and 45.5 g/kg) on these variables (shell weight, specific gravity and number of eggs discarded) of white egg layers at 57 weeks of age, and by Pelícia et al (2009a), who also did not find differences in shell thickness, number of eggs discarded and in the specific gravity of the eggs from second-cycle brown egg layers in function of the four calcium levels (30; 35; 40 and 45 g/kg) studied. However, Safaa et al (2008) reported improvement in the shell thickness of eggs with calcium at the level of 40 g/kg in comparison with 35 g/kg, keeping the calcium:phosphorus ratio at 12:1, in a diet for brown egg layers in the period from 58 to 73 weeks of age.…”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…The results for shell weight, specific gravity and number of eggs discarded are similar to those obtained by Murata et al (2009), who also did not observe influence from the calcium levels (37.5; 41.5 and 45.5 g/kg) on these variables (shell weight, specific gravity and number of eggs discarded) of white egg layers at 57 weeks of age, and by Pelícia et al (2009a), who also did not find differences in shell thickness, number of eggs discarded and in the specific gravity of the eggs from second-cycle brown egg layers in function of the four calcium levels (30; 35; 40 and 45 g/kg) studied. However, Safaa et al (2008) reported improvement in the shell thickness of eggs with calcium at the level of 40 g/kg in comparison with 35 g/kg, keeping the calcium:phosphorus ratio at 12:1, in a diet for brown egg layers in the period from 58 to 73 weeks of age.…”
Section: Resultssupporting
confidence: 87%
“…Considering the productive performance of white egg layers under production, Dantas et al (2010) suggested the calcium et al (2012), at 43.1 g/kg in the diet. As for the effects from the calcium:phosphorus ratios on the productive performance of white egg layers, they were similar to those found by Lelis et al (2009), who studied available phosphorus at the levels of 2.3; 2.9; 3.5; 4.1 and 4.7 g/kg in diets with calcium at 42 g/kg (calcium: phosphorus ratio varying from 18.26 to 8.93:1) for brown egg layers in the period from 50 to 66 weeks of age and did not verify difference in the performance of the animals; and by Rosa et al (2011), who studied the calcium:phosphorus ratios of 8:1; 11:1 and 14:1 for brown egg layers in the period from 28 to 36 weeks of age and also did not observe effect from the calcium:phosphorus ratios on feed intake, egg laying rate, feed conversion per egg mass and egg weight.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly [45] noted variation in FCR and stated that FCR is highly dependent on the number of eggs produced (51%) followed by feed consumption (31%). Likewise, increased nutrient density (energy, amino acids, Ca and available P) linearly improved FCR from 2.12 to 1.91 resulting in a 9.9% improvement in feed conversion [46,47] also reported that increased blood Ca ++ concentration improved FCR per dozen of eggs (Appendix).…”
Section: Feed Conversion Ratiomentioning
confidence: 99%
“…Increasing phosphorus from 0.044 to 0.088% (T0 to T2) in feed had no effect on the phosphorus intake, but the increase of phosporus by 0.13% (T0 to T3) increased phosphorus intake significantly (Table 2). Pelicia et al (2009) reported that calcium and phosphorus intake is influenced by the calcium and phosphorus level of feed. Increasing calcium of the feed by 3-5% increased calcium intake 1.77 g/hen/day and increasing phosphorus of feed from 0.25 to 0.4% increase phosphorus intake to 0.19 mg/hen/day.…”
Section: Calcium and Phosphorus Intakementioning
confidence: 99%